Vulnerability to terrorist attacks in European electricity decarbonisation scenarios: Comparing renewable electricity imports to gas imports - Lilliestam, Johan (Energy Policy, 2014)
The decarbonised future European electricity system must remain secure: reliable electricity supply is a prerequisite for the functioning of modern society. Scenarios like Desertec, which partially rely on solar power imports from the Middle East and North Africa, may be attractive for decarbonisation, but raise concerns about terrorists interrupting supply by attacking the long, unprotected transmission lines in the Sahara. In this paper, I develop new methods and assess the European vulnerability to terrorist attacks in the Desertec scenario. I compare this to the vulnerability of today's system and a decarbonisation scenario in which Europe relies on gas imports for electricity generation. I show that the vulnerability of both gas and electricity imports is low, but electricity imports are more vulnerable than gas imports, due to their technical characteristics. Gas outages (and, potentially, resulting blackouts) are the very unlikely consequence even of very high-number attacks against the gas import system, whereas short blackouts are the potential consequence of a few attacks against the import electricity lines. As the impacts of all except extreme attacks are limited, terrorists cannot attack energy infrastructure and cause spectacular, fear-creating outages. Both gas and electricity import infrastructure are thus unattractive and unlikely terrorist targets. © 2013 Elsevier Ltd.
CRIS-Team Scopus Importer:2023-06-14
Keywords: Critical infrastructure; Decarbonisation; Terrorism